In-Situ Grown Ni(OH)2 Nanosheets on Ni Foam for Hybrid Supercapacitors with High Electrochemical Performance. Issue 5 (23rd March 2018) - Guo, Jing; Zhao, Yingyuan; Jiang, Nian; Liu, Anmin; Gao, Liguo; Li, Yanqiang; Wang, Hongxia; Ma, Tingli
Abstract : In-suit grown composite materials have received much attention on scientific communities in recent years owing to their unique physicochemical properties for applications such as energy storage devices. Herein, we report freestanding in-situ grown Ni(OH)2 nanosheets on Ni foam by a facile one-step hydrothermal approach using aqueous nickel nitrate as precursor solution without any additives. The influence of concentration of nickel nitrate on morphology and electrochemical properties of the synthesized Ni(OH)2 /Ni foam (NHNF) was investigated. Binder-free 0.12-NHNF electrode material exhibited a high gravimetric capacity of 340 mAh g −1 at a current density of 1 A g −1, excellent cycling stability (81.1% capacity retention after 3000 cycles) and good flexibility (89.2% capacity retention after folding in a roll). A hybrid supercapacitor (HSC) based on the synthesized 0.12-NHNF as positive electrode and commercial active carbon as negative electrode delivered a high energy density of 39.2 Wh kg −1 at a power density of 598 W kg −1 at a working voltage of 1.6 V. Long-term cycling stability test shows that the capacity retention of 84.3% was achieved with the HSC after 3000 cycles. The excellent electrochemical performance of the NHNF material indicates that it can be an appealing candidate electrode material in energy storage devices.